2022
DOI: 10.33394/jk.v8i2.5065
|View full text |Cite
|
Sign up to set email alerts
|

Digital Literacy Analysis on Online Learning Outcomes for Macroeconomics with Gender-Mediated and Family Socio-economics as Moderating Variables

Abstract: This study aims to analyze whether digital literacy simultaneously and significantly affects academic learning outcomes mediated by gender in students, whether digital literacy simultaneously and significantly affects academic learning outcomes moderated by the socio-economic family of students, and whether digital literacy simultaneously and significantly affects academic learning outcomes mediated by gender and family socio-economics as a moderator for macroeconomics students. By using a quantitative method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…However, existing research revealed that gender difference in education was still impactful on many aspects of learning and teaching (Pekkarinen, 2012;Permanyer & Boertien, 2019;Steegh et al, 2019). Specifically, contrary findings regarding the level of self-perceived digital literacy between gender groups were reported from previous studies in various educational settings (Katsarou, 2021;Syamiya et al, 2022). As students' level of digital literary in translation training programs were insufficient studied, documented cases of the comparison of digital literary between different gender groups of translation trainees were consequently hardly accessible.…”
Section: Digital Literacy For Translatorsmentioning
confidence: 91%
“…However, existing research revealed that gender difference in education was still impactful on many aspects of learning and teaching (Pekkarinen, 2012;Permanyer & Boertien, 2019;Steegh et al, 2019). Specifically, contrary findings regarding the level of self-perceived digital literacy between gender groups were reported from previous studies in various educational settings (Katsarou, 2021;Syamiya et al, 2022). As students' level of digital literary in translation training programs were insufficient studied, documented cases of the comparison of digital literary between different gender groups of translation trainees were consequently hardly accessible.…”
Section: Digital Literacy For Translatorsmentioning
confidence: 91%
“…Penelitian dari Raharjo & Winarko (2021) juga menunjukkan hal yang sama seperti Syamiya et al, (2022) tentang literasi digital dalam dunia pendidikan menjadi hal yang sangat penting saat ini, karena kemampuan lulusan dalam literasi digital diperlukan di semua disiplin ilmu (Reyna et al, 2018). Menurut Asni Aulia et al, (2021 literasi digital yaitu kebisaan yang dimiliki seseorang untuk mempraktekan TIK, menemukan, membuat, evaluasi, memanfaatkan, dan informasi, dengan kecakapan kognitif maupun teknikal.…”
unclassified
“…Kekhawatiran tersebut yaitu tenaga kerja manusia akan digantikan oleh tenaga mesin yang telah muncul secara bertahap semenjak awal revolusi industry, yang menjadi penggerak utama dari revolusi teknologi yang sedang berlangsung yaitu teknologi informasi dan komunikasi (TIK) (Soniansih et al, 2021). Wulandari et al(2022), melihat adanya teknologi terutama literasi digital akan meningkatkan komunikasi secara intensif dlaam berbagai kondisi dan ekspresi di media. Tindakan social yang konstruktif, refleksi diri dan realisasi pengetahuan baru.…”
unclassified